Effects of yoga in modifying blood pressure in patients of type 2 diabetes mellitus - Shrivastava, Namita; Maheswari, Basant Kumar; Rath, Debapriya; Sarkar, Debashree (International Journal of Research in Medical Sciences, 2018)
Background: The incidence of diabetes mellitus is increasing with the increase in unhealthy dietary habits, physical inactivity and sedentary lifestyle. Hypertension complicated with diabetes further aggravates the problem. Yoga has been found to be helpful in delaying the progression and complications of the disease. The present study was undertaken with an aim to evaluate the effect of yoga in modifying blood pressure in patients of diabetes mellitus. Methods: Thirty patients of diabetes mellitus who were known case of hypertension were taken and their fasting and post-prandial blood glucose levels, systolic and diastolic blood pressure and waist circumference were analysed before and after ninety days of yoga in the department of physiology and biochemistry. Results: Systolic and diastolic blood pressure, waist circumference and fasting and post-prandial blood glucose level showed significant reduction (p value <0.05). Conclusions: This study emphasizes the importance of yoga in the control and management of type 2 diabetes mellitus and hypertension.